Penegakan Hukum Terhadap Eksploitasi Anak Yang Dijadikan Pembantu Rumah Tangga Menurut Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan Di Wilayah Hukum Kepolisian Resor Kota Pekanbaru - Sutrisno '; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Human rights are basic rights that are inherently human, universal, and bestowed byGod Almighty. In the protection of human rights, children are also included. A child is a personwho is not yet 18 (eighteen) including a child still in the womb. Child protection efforts shouldstart as early as possible, but the reality is still often heard by children as domestic workers. InIndonesia there is an independent State institution whose function is to protect and improve thewelfare of children, the institution is the Indonesian Child Protection Institution, while for theprovince of Riau is the Child Protection Agency of Riau Province. Based on data obtained fromPekanbaru Police on the issue of child protection in Pekanbaru City, many cases of child abuseoccur every year, and the most numerous cases are child cases as labor and the number of caseshas always increased in the last three years. In this case relate to the settlement of cases ofchildren who become victims of crime of economic exploitation in Pekanbaru City by PolrestaPekanbaru. The purpose of writing this thesis, namely First, Accountability of child crime as adomestic worker in Pekanbaru City by Pekanbaru Police, Second, Obstacles encountered whocan be asked accountability of children as victims of crime of economic explanation inPekanbaru City by Pekanbaru Police, Third, Efforts are made to overcome obstacles fromImplementation of accountability of child crime as domestic worker by Polresta Pekanbaru.This type of research can be classified in the type of sociological juridical research,because in this study the authors directly conduct research on the location or place studied toprovide a complete and clear picture of the problem under study. This research was conductedat Polresta Pekanbaru City, while population and sample are all parties related to the problemstudied in this research, data source used primary data, secondary data, and tertiary data, datacollecting technique in this research is done by questionnaire, Interviews, and literature review.From the results of research problems there are three main things that can be concluded.Firstly, the implementation of legal protection in the handling of child rights violation casesconducted by Polresta Pekanbaru is in the form of non penalty efforts to assist the child victims,and assist the child in the recovery process both psychologically and socially by psychologist.Second, the obstacles faced by Polresta Pekanbaru from the implementation of law enforcementon children as victims of economic exploitation there are 2 (two) factors that are internal factorsand external factors. Third, efforts made by Pekanbaru Police in overcoming obstacles from theimplementation of legal protection against children as victims of economic exploitation inPekanbaru City has two efforts namely preventive efforts and repressive efforts. SuggestionWriter, First, In preventing and combating the crime of economic exploitation of childrenexpected to continue to do preventive efforts such as socialization, workshop, and others.Second, the legal protection of children as victims of economic exploitation conducted byPolresta Pekanbaru need to fix the internal factors and external factors.Keywords: Accountability-Child-Victim-Victim- Economic Exploitation